From molecules to medicines: the dawn of targeted therapies for genetic epilepsies. Issue 12 (December 2018) - Demarest, Scott; Brooks-Kayal, Amy
Abstract Precision medicine is the treatment of patients with therapy targeted to their specific pathophysiology. This lofty ideal currently has limited application in clinical practice. However, new technological advances in epilepsy models and genomics suggest that the precision medicine revolution is closer than ever before. We are gaining an improved understanding of the true complexity underlying the pathophysiology of genetic epilepsies and the sources of phenotypic variation that continue to frustrate efforts at genotype–phenotype correlation. Conventional experimental models of epilepsy, such as mouse models and heterologous expression systems, have provided many of the advances in our understanding of genetic epilepsies, but fail to account for some of these complexities. Novel high-throughput models of epilepsy such as zebrafish and induced pluripotent stems cells can be combined with CRISPR–Cas9 gene editing techniques to explore the pathogenesis of a specific gene change and rapidly screen drug libraries for potential therapeutics. The knowledge gained from these models must be combined with thorough natural history studies to determine appropriate patient populations for pragmatic clinical trials. Advances in the 'omics', genetic epilepsy models and deep-phenotyping techniques have revolutionary translational research potential that can bring precision medicine to the forefront of clinical practice in the coming decade. New technological advances in genomics have enabled the rapid discovery of hundreds of gene mutations linked to epilepsy. This Review considers the prospects for precision medicine in genetic epilepsies, the use of conventional and novel experimental models to unpick the complex pathogenic mechanisms of these diseases and the opportunities and challenges that face basic and clinical researchers. Key points Efforts to develop precision medicine for epilepsy have been limited by the complexity of the pathophysiology underlying genotype–phenotype correlations. A complete picture of genetic epilepsy pathogenesis recognizes the contribution of intragenic, cellular and network-level variability that is influenced by genomic and environmental differences between patients. Conventional models of epilepsy (heterologous expression systems and mouse models) can address some of these layers of complexity but fail to address others. New models of epilepsy (such as zebrafish and induced pluripotent stem cells) offer insights that were previously not possible. Complementary preclinical approaches that include both conventional and novel models of epilepsy have the power to advance research in precision medicine like never before. The combination of these robust preclinical developments with collaborative clinical research, including deep phenotyping and pragmatic clinical trials, has the potential to improve precision treatment of the genetic epilepsies.